Pengaruh Metode Guided Writing Terhadap Kemampuan Menulis Teks Cerita Fiksi Siswa Kelas V SD Muhammadiyah Perumnas Kota Makassar - Muhammad Zulkifli; Munirah; Abdan Syakur (STKIP Subang, 2026)
This study aims to determine the effect of the guided writing method on fifth-grade elementary school students’ ability to write fictional narrative texts. This research was motivated by students’ low ability to develop story ideas, organize text structure coherently, and use appropriate vocabulary and language conventions. The study employed a quantitative approach using a quasi-experimental method (pre-experimental design) with a one group pretest–posttest design. The research subjects consisted of 20 fifth-grade students at SD Muhammadiyah Perumnas Makassar. Data were collected through a fictional narrative writing test, while data analysis techniques included descriptive and inferential statistical analysis using a paired sample t-test. The results showed that the average score of students’ fictional narrative writing skills increased from 56.35 in the pretest to 82.15 in the posttest. The hypothesis testing results indicated a significance value (Sig.) of 0.000 < 0.05, which means that there was a significant effect of the guided writing method on students’ ability to write fictional narrative texts. All students achieved learning mastery at the posttest stage. These findings indicate that the guided writing method is effective in improving elementary school students’ ability to write fictional narrative texts.